Smart city business model approach: the role of opportunities, values, and advantages. - Perätalo, Sari; Ahokangas, Petri; Iivari, Marika (Innovation: The European Journal of Social Sciences, 2025)
The purpose of this research is to explore the role of the business model approach in the smart city context by examining the business model antecedents: opportunities, values, and advantages. By applying the business model approach, we examine the dynamics of replicability, scalability, and sustainability of digital solutions in smart cities. Based on the participatory action research method, this study utilizes data collected during 2018–2020 from the European Union's Digital Transition Partnership meetings and workshops. The objective of the partnership was to create an EU-level Action Plan for European cities for digital transition. The research findings indicate the importance of recognizing the antecedents to business models when using them as a strategic development tool for smartening cities. The proposed business model approach can support the continuous development of digitalization-related opportunities and solutions in cities.